The delivery of Primary Health Care in remote communities: A Grounded Theory study of the perspective of nurses. (February 2020) - McCullough, Kylie; Whitehead, Lisa; Bayes, Sara; Williams, Anne; Cope, Vicki
Abstract: Background: Australia has vast areas of desert, wilderness and offshore islands where nurses provide the majority of health care services. The residents of Australia's remote communities generally have poorer health status than their metropolitan counterparts. Despite recognition of Primary Health Care as a comprehensive model of acute and preventative care well suited to areas of high health and social need, there is little known about how nurses employ the Primary Health Care model in practice. Objectives: This study described and explained from the perspective of nurses, the actions and interactions involved in the delivery of Primary Health Care in remote communities. Design: This study was conducted from a Constructivist Grounded Theory perspective. Settings: The setting was community health centres or Aboriginal Medical Services located in 'remote' or 'very remote' areas. Communities with inpatient health services were excluded. Participants: Twenty four Nurse Practitioners, Registered Nurses and nursing academics participated. Participants had worked or were working, in a variety of remote communities across Australia. Length of service ranged from three months to over 15 years nursing in remote areas. Methods: Data were collected through 23 telephone interviews and an expert reference group. Theoretical sampling and constant comparative analysis were used to reach theoretical saturation. Results: The core issue participants faced was the inability to provide Primary Health Care. Four conditions impacted on the core issue: understanding the social world of the remote community, availability of resources, clinical knowledge and skill and, shared understanding and support . The process of doing the best you can with what you have, emerged as the way participants dealt with the inability to provide Primary Health Care. The process involved four primary activities: facilitating access to health care, continually learning, seeking understanding, and home-making in a work environment. The outcome of this process was considered to be making compromises to provide Primary Health Care . Conclusions: This study describes the substantive theory: making compromises to provide Primary Health care services in the remote Australian setting. Understanding the process of making compromises could direct employers and educators in their efforts to improve the provision of Primary Health Care in a variety of settings. Increased attention to the education, resources and support of nurses is likely to increase access to safe, quality care for remote communities.